Meaning Nature and Scope of Managerial Economics - Alka (Innovative Research Thoughts, 2017)
The science of Managerial Economics has emerged only recently. With the growing variability and unpredictability of the business environment, business managers have become increasingly concerned with finding rational and ways of adjusting to an exploiting environmental change. The problems of the business world attracted the attentions of the academicians from 1950 onwards. Managerial economics as a subject gained popularity in the USA after the publication of the book “Managerial Economics” by Joel Dean in 1951. Managerial economics generally refers to the integration of economic theory with business practice. Economics provides tools managerial economics applies these tools to the management of business. In simple terms, managerial economics means the application of economic theory to the problem of management. Managerial economics may be viewed as economics applied to problem solving at the level of the firm. It enables the business executive to assume and analyse things. Every firm tries to get satisfactory profit even though economics emphasises maximizing of profit. Hence, it becomes necessary to redesign economic ideas to the practical world. This function is being done by managerial economics.